QUALITY OF LIFE OF CHILDREN WITH CHRONIC DISEASES - A.G. Timofeeva; I.V. Vinyarskaya ("Paediatrician" Publishers LLC, 2008)
An urgency of studying of quality of life in clinical pediatrics is described in this article. Some results of trials, studying quality of life of children with chronic diseases was presented. These results include information of influence of chronic disease, peculiarities of quality of life in patients with different nosologic forms, long9term disorders of quality of life. Key words: children, quality of life, chronic diseases.